The Effects of Telehealth During Pregnancy on Maternal Knowledge and Postpartum Mental Health in the Covid-19 Pandemic - Wahyul Anis; Rize Budi Amalia (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: The Covid-19 pandemic caused changes in health services, especially Antenatal Care (ANC)because pregnant women are at risk of contracting Covid-19 so telehealth is one of the methods developedto make ANC more effective and efficient. This study aimed to analyze the relationship between telehealthduring pregnancy on knowledge and mental health of postpartum mothersMethods : The research method uses a case-control where there are two groups of samples. The case groupconsisted of 30 postpartum mothers who received telehealth (routine online monitoring and counseling)during pregnancy, while the control group consisted of 27 postpartum mothers who did not receivetelehealth during pregnancy. Samples were taken using a random sampling technique with inclusion criteriaare postpartum mothers who received online monitoring and counseling during pregnancy routinely byvolunteer mothers. The exclusion criteria were postpartum mothers who did not routinely receive onlinemonitoring and counselling. Statistical analysis used Wilcoxon Mann Whitney, Chi-Square, and FisherExact tests.Conclusions:The telehealth has influenced the maternal knowledge but it will necessary to develop atelehealth strategy that contribute to the mental health of mother during the postpartum period.